The Relationship between VIII Grade of Depok Junior High School Students’ Vocabulary Mastery and the Results of Reading English - Vickry Ramdhan (Candradimuka: Journal of Education, 2023)
The purpose of this study was to determine the relationship between vocabulary mastery and the results of learning to read English. The research method used to analyze was a correlational descriptive method. The instruments used were in the form of a vocabulary mastery test totaling 40 questions and an English reading learning achievement test totaling 40 questions after the validity test was carried out and the instrument test was reliable which was tested on 50 samples. From the research results of the Vocabulary Mastery test, the results of the Mean (M) analysis were 26.32; The median (Me) is 34; Mode (Mo) of 21; Variant (V) 83.1776 and Standard Deviation (SD) of 9.1. From the results of the English Reading Results test, the Mean (M) was 25.4, the Median (Me) was 37, the Mode (Mo) was 38.75, the Variant (V) was 121.64 and the Standard Deviation (SD) was 11.02905254. From the calculation of hypothesis testing, it is obtained that t value = 5.4 > t table = 2.484 So it can be concluded that H0 is rejected H1 is accepted. It means if there is a positive and significant relationship between the Vocabulary Mastery variable on Reading Learning Outcomes.